A study of laparoscopic instrument use during colorectal surgery. (July 2019) - White, Eoin J.; McMahon, Muireann; Walsh, Michael T.; Coffey, J. Calvin; O'Sullivan, Leonard W.
Abstract: The aim of this study was to quantify laparoscopic instrument use and actions of both limbs during a sample of common colorectal surgical procedures. A method was devised using Observer XT software to code video recordings. Anonymised HD video recordings of nine laparoscopic colorectal procedures performed by a single surgeon were analysed. We determined the percentage and frequency of instrument use and limb actions throughout the total laparoscopic surgical duration, as well as the duration of instrument inactivity. Seven instruments and seven actions were studied across nine surgical procedures. Manoeuvring, blunt dissection, and tenting up tissues accounted for the longest amount of total surgical time (non-dominant hand (NDH) 29%, dominant hand (DH) 39%), followed by grasping (NDH 33%, DH 9%), and cauterising (NDH <0.2%, DH 8%). Least time was spent performing other actions such as suction/irrigation (NDH 0.01%, DH 3%) and stapling colorectal tissue (NDH 0.03%, DH 0.5%). The total duration of instrument use and hand actions by the dominant and non-dominant hands were similar overall. However, the frequency of actions performed was lower for the non-dominant hand. This indicates that the non-dominant hand spent more time holding actions than switching between actions, supporting the actions of the dominant hand. These findings highlight the lengthy durations of laparoscopic surgical procedures involved in navigating to anatomical planes and moving tissues. Further, the results detail the extent of secondary functions performed with the surgical instruments. Highlights: We use laparoscopic video data to study hand use and instrument actions during twelve laparoscopic surgeries completed by two surgeons. The Observer XT was used to conduct the study, and has been used for other Human Factors studies. The method employed successfully mapped hand actions and instrument use. There is a clear pattern of instrument usage throughout all procedures studied, the frequent actions being manoeuvring and grasping; however, the manoeuvring action encompassed actions such as holding or "tenting up" anatomy and blunt dissection. Generally, the dominant and non-dominant hand action durations were similar when averaged across the procedures, with the exception of the laparoscopic sigmoid colectomy.